Legal organization of cycling, the opportunity to develop agro tourism in Romania - Florescu, Georgiana; Camelia, Toma; Lepădatu Ion, Cristian (Economics of Agriculture, 2010)
Presently, the Ministry of Tourism is under way to promote a law to introduce in our country as well a form of tourism successfully practiced in western countries, namely the cycling tourism. One can state that cycling tourism is even nowadays practiced in Romania, but on an un-organized basis and on routes that are not homologated. The development and promotion of this form of tourism can provide to some rural and agricultural pensions in the country new possibilities for attracting customers, due to the fact that tourists going on cycling tours will need hosts to rest and taste the traditional Romanian food.